Oral Mucosal Adhesive Films Containing Royal Jelly Accelerate Recovery From 5-Fluorouracil-Induced Oral Mucositis - Shinichi Watanabe; Katsuya Suemaru; Kenshi Takechi; Hiroaki Kaji; Kimie Imai; Hiroaki Araki (Elsevier, 2013)
Oral mucositis induced by chemotherapy or radiotherapy has an impact upon quality-of-life, is dose-limiting for chemotherapy, and causes considerable morbidity. We evaluated the effect of royal jelly (RJ) on 5-fluorouracil (5-FU)-induced oral mucositis in hamsters. Oral mucositis was induced in hamsters through a combination of 5-FU treatment and mild abrasion of the cheek pouch. RJ was contained in chitosan-sodium alginate film (RJ film). Films were attached to the oral mucosa and the healing process examined by measuring the area of mucositis, myeloperoxidase (MPO) activity, microscopic aspects, and RT-PCR for detection of pro-inflammatory cytokines (tumor necrosis factor-α, interleukin-1β). Furthermore, we evaluated the radical-scavenging activity of RJ and generation of keratinocyte growth factor from human periodontal ligament fibroblasts. RJ films (10%, 30%) significantly improved recovery from 5-FU-induced damage, reduced MPO activity and the production of pro-inflammatory cytokines. Additionally, RJ showed radical-scavenging activity. These data suggest that topical application of films that contain RJ had a healing effect on the severe oral mucositis induced by 5-FU and that the effect was caused by the anti-inflammatory or anti-oxidative activities of RJ. Keywords:: antioxidant, cancer, 5-fluorouracil, oral mucositis, royal jelly